A CONTRIBUIÇÃO DO PEDAGOGO EM ESPAÇOS FORA DA ESCOLA - Silva, Terezinha de Jesus Amaral da (2009)
This study concentrated efforts to examine the contribution of the teacher in implementation of social welfare developed by SEMCAS - Municipal Department of Children and Social Welfare has the task of developing, coordinating and implementing programs and projects according to the quality of life to guarantee basic rights for the people most in need of São Luís This institution is built on area of educational performance, education outside the school. Emphasize the contribution of the teacher in programs and projects of SEMCAS, based on conceptions of education in the broadest sense, not restricting it to the formal space of the school. These concepts that refer to non-school education in the spaces outside the school that is configured as opportunities for professional educators. Was taken as starting point for the analysis of the crisis of capital, in the 70s and its impacts in Brazilian social policies, considering the changes in the international arena, with significant repercussions on the national scene and their impacts on social institutions. Try to capture these impacts in policies developed by the institution concerned. To achieve the purpose of this work, was necessary to also examine the role of the state and of social policies, understood from the neoliberal context. From the methodological point of view, we chose a method of qualitative analysis in the efforts to capture the contradictions of reality on the contribution of the teacher in an institution of this nature, from the point of view of an unequal society and further studies indicate that the routing of these contradictions.